2001
DOI: 10.1016/s0014-5793(01)03264-1
|View full text |Cite
|
Sign up to set email alerts
|

Potent transforming activity of the small GTP‐binding protein Rit in NIH 3T3 cells: evidence for a role of a p38γ‐dependent signaling pathway

Abstract: A novel branch of the Ras family, Rit, was recently identified. Rit exhibits a distinct C-terminus and effector domain, and does not activate mitogen-activated protein kinase (MAPK) but can cooperate with Raf to transform fibroblasts. Here, we found that when overexpressed, activated mutants of Rit transform NIH 3T3 cells efficiently, and stimulate p38Q Q but not MAPK, p38K K, p38L L, p38N N, or ERK5. Furthermore, we provide evidence that p38Q Q activation is required for the ability of Rit to stimulate gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 15 publications
3
30
0
Order By: Relevance
“…The SRE activity was determined as described previously (Sakabe et al, 2002). Briefly, HEK-293T cells plated in a sixwell plate together with 0.1 mg of pSRE Luc reporter plasmid.…”
Section: Reporter Gene Assaymentioning
confidence: 99%
“…The SRE activity was determined as described previously (Sakabe et al, 2002). Briefly, HEK-293T cells plated in a sixwell plate together with 0.1 mg of pSRE Luc reporter plasmid.…”
Section: Reporter Gene Assaymentioning
confidence: 99%
“…NIH3T3 cells were maintained in Dulbecco's modified Eagle's medium (Life Technologies) supplemented with 10% calf serum, and transfected by the calcium-phosphate precipitation technique adjusting the total amount of DNA to 1 mg/plate with vector alone (Sakbe et al, 2002). Mass populations of cells expressing the transfected gene were selected for their ability to grow in the presence of Geneticin (G418) (GIBCO BRL, NY, USA).…”
Section: Cell Lines and Transfectionmentioning
confidence: 99%
“…Of interest, we and others have recently (Rusyn et al, 2000;Sakbe et al, 2002) reported that the newest member of the Ras superfamily, Rit (Ras-like protein in tissues), induces Ras-like foci when its activated mutant, Rit 79L (analogous to the oncogenic mutant H-Ras 61L), is expressed in NIH3T3 cells. Rit was cloned as a homolog of Ric (calmodulin-binding Ras-like GTPase) in Drosophila (Wes et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations